Solvent modulation in peptide sub-microfibers obtained by solution blow spinning - Dias, Ana Margarida Gonçalves Carvalho; Cena, Cícero; Lutz-Bueno, Viviane; Mezzenga, Raffaele; Marques, Ana; Ferreira, Isabel; Roque, Ana Cecília Afonso (Frontiers in Chemistry, 2022)
Peptides possess high chemical diversity at the amino acid sequence level, which further translates into versatile functions. Peptides with self-assembling properties can be processed into diverse formats giving rise to bio-based materials. Peptide-based spun fibers are an interesting format due to high surface-area and versatility, though the field is still in its infancy due to the challenges in applying the spinning processes developed for forming polymer and protein fibers to peptides. In this work we show the use of solution blow-spinning to produce peptide fibers. Peptide fiber formation was assisted by the polymer poly (vinyl pyrrolidone) (PVP) in two solvent conditions. Peptide miscibility and further self-assembling propensity in the solvents played a major role in fiber formation. When employing acetic acid as solvent, peptide fibers (0.5 μm) are formed around PVP fibers (0.75 μm), whereas in isopropanol only one type of fibers are formed, consisting of mixed peptide and PVP (1 μm). This report highlights solvent modulation as a mean to obtain different peptide sub-microfibers via a single injection nozzle in solution blow spinning. We anticipate this strategy to be applied to other peptides with self-assembly propensity to obtain multi-functional proteinaceous fibers.